Impact of Disease Duration on Vascular Surrogates of Early Atherosclerosis in Childhood‐Onset Systemic Lupus Erythematosus. Issue 1 (January 2016) - Barsalou, Julie; Bradley, Timothy J.; Tyrrell, Pascal N.; Slorach, Cameron; Ng, Lawrence W. K.; Levy, Deborah M.; Silverman, Earl D.
Abstract : Objective: To determine whether longer disease duration negatively impacts carotid intima‐media thickness (CIMT), flow‐mediated dilation (FMD), and pulse wave velocity (PWV) in a cohort of patients with childhood‐onset systemic lupus erythematosus (SLE), and to compare CIMT, FMD, and PWV in patients with childhood‐onset SLE with those in healthy children and explore determinants of vascular test results in childhood‐onset SLE. Methods: Cross‐sectional analysis was performed in a prospective longitudinal cohort of patients with childhood‐onset SLE at the latest followup visit. Clinical and laboratory data were collected for patients with childhood‐onset SLE. CIMT, FMD, and PWV were measured using standardized protocols in patients with childhood‐onset SLE and healthy children. Correlations between disease duration and results of the 3 vascular tests were performed. Vascular data in patients with childhood‐onset SLE were compared with those in healthy children. Multivariable linear regression was used to identify determinants of CIMT, FMD, and PWV in childhood‐onset SLE. Results: Patients with childhood‐onset SLE (n = 149) and healthy controls (n = 178) were enrolled. The median age of the patients was 17.2 years (interquartile range [IQR] 15.7–17.9 years), and their median disease duration was 3.2 years (IQR 1.8–4.9 years). The median age of the healthy children was 14.7 years (IQR 13.1–15.9 years). Longer disease duration correlated with worse FMD (r = −0.2, P  = 0.031) in patients with childhood‐onset SLE. Patients with childhood‐onset SLE had smaller (better) CIMT, higher (better) FMD, and similar PWV compared with healthy controls. Linear regression analysis explained <24% of the variation in vascular test results in patients with childhood‐onset SLE, suggesting that other variables should be explored as important determinants of CIMT, FMD, and PWV. Conclusion: In this cohort of 149 patients with childhood‐onset SLE, patients did not have worse CIMT, FMD, or PWV than did healthy controls. Longer disease duration was associated with worse FMD, suggesting progressive endothelial dysfunction over time.